TRANSLATION TECHNIQUES AND TRANSLATION IDEOLOGIES OF CULTURE SPECIFIC ITEMS IN THE NETFLIX DOCUMENTARY STREET FOOD: USA - Feby Apriola; Andy Bayu Nugroho (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates and classifies culture-specific items in the Netflix documentary Street Food: USA, along with the translation techniques and ideologies applied. This research employed a descriptive qualitative method. The data source was the Netflix documentary Street Food: USA, using English and Indonesian subtitles as target language. A total of 164 data containing culture-specific items were analyzed. The study draws on Newmark’s (1988) theory for culture-specific items, Molina and Albir’s (2002) framework for translation techniques, and Venuti’s (2004) concept of translation ideology. Data were analyzed using translation equivalence and distributional methods. All categories of culture-specific items were identified in the subtitles. Material culture dominated (95 instances), followed by social organization (39), social culture (28), and ecology (1). Nine of eighteen techniques were identified. Pure borrowing was most frequent (78), followed by literal translation (36), adaptation (10), reduction and amplification (3), and particularization and calque (1). The dominant couplet technique was literal + pure borrowing (12). Foreignization dominated (145), while domestication appeared in 19. These findings contribute to audiovisual translation studies by demonstrating how subtitle translators negotiate cultural preservation and audience accessibility in documentary contexts.